A study of the effects of metformin, a biguanide derivative, on annulus fibrosus and nucleus pulposus cells - Kaya, Yasin Emre; Karaarslan, Numan; Yılmaz, İbrahim; Yaşar Şirin, Duygu; Akalan, Hande; Özbek, Hanefi (Turkish Neurosurgical Society, 2020)
AIM: To investigate the effects of metformin, a drug used widely for the treatment of type 2 diabetes mellitus, on human primary cell cultures prepared from uninjured segment of disc material intervertebral disk tissues.MATERIAL and METHODS: Primary cell cultures were prepared using the tissues of six patients (three males and three females) who had undergone lumbar microdiscectomy and sequestrectomy. Untreated samples served as the control group, and metformintreated samples served as the experimental group. All the samples were evaluated using an inverted light microscope, acridine orange/propidium iodide staining (AO/PI), and a fluorescence microscope. The cytostatic and cytotoxic effects of metformin, which was administered to the samples using a commercial MTT assay kit, were also evaluated. The data obtained were statistically assessed, and the alpha significance value was accepted as less than 0.05. In addition, for the groups' changes in the expressions of chondroadherin (CHAD), cartilage oligomeric matrix protein (COMP), interleukin-1 beta (IL-1 beta) matrix metalloproteinase 7 (MMP-7), and matrix metalloproteinase 19 (MMP-19), genes related to the extracellular matrix synthesis and degradation were determined using gene-specific TaqMan Gene Expression Assays.RESULTS: The administration of the drug adversely affected nucleus pulposus (NP)/annulus fibrosus (AF) cells and extracellular matrix-like structures. This was statistically significant (p<0.05).CONCLUSION: Clinicians should not disregard the adverse effects of metformin, which is used widely in clinical practice, on the components of intervertebral disk tissues.
Keywords: Annulus Fibrosus; Intervertebral Disc Tissue; Metformin; Nucleus Pulposus; Primary Human Cell Culture